Analisis Sistem Pengendalian Intern Atas Pembayaran Gaji dan Upah pada PT Perkebunan Nusantara XII - Amira Qonita; Muslimin Muslimin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the analysis of the internal control system for the payment of salaries and wages. The type of research conducted is descriptive method, this research uses qualitative. Sources of primary data in this study in the form of interviews from the parties concerned at PT. Nusantara XII Plantation Surabaya. The results showed that PT. Perkebunan Nusantara XII did not experience problems with the salary and wage payment system. This is evidenced by the division of tasks for each section and also a healthy practice. The implementation of the internal control system for payment of salaries and wages has been going very well, where in its application there are incentives for company policies to achieve goals and all employees are required to comply and there are sanctions for employees who do not comply. Keywords: analysis of internal control systems, payment of salaries and wages